1999
DOI: 10.1074/jbc.274.28.19852
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of C1 and C2 Domains of Protein Kinase C-α in Its Membrane Binding and Activation

Abstract: The regulatory domain of conventional protein kinase C (PKC) contains two membrane-targeting modules, the C2 domain that is responsible for Ca 2؉ -dependent membrane binding of protein, and the C1 domain composed of two cysteine-rich zinc fingers (C1a and C1b) that bind diacylglycerols and phorbol esters. To understand the individual roles and the interplay of the C1 and C2 domains in the membrane binding and activation of PKC, we functionally expressed isolated C1 and C2 domains of PKC-␣ and measured their ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
184
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 157 publications
(205 citation statements)
references
References 53 publications
19
184
2
Order By: Relevance
“…Differential DAG Affinity of C1A and C1B Domains-Our previous studies indicated that the C1A domain plays a critical role in the DAG-induced membrane binding and activation of PKC␣ (38,65), whereas both the C1A and C1B domains of PKC␥ participate in these processes (38). This is ascribed to the fact that the C1A domain of PKC␣ has higher DAG affinity, whereas both the C1A and C1B domains of PKC␥ have comparable DAG affinity and conformational flexibility.…”
Section: Phosphatidylserine (Ps)-specific Membranementioning
confidence: 96%
“…Differential DAG Affinity of C1A and C1B Domains-Our previous studies indicated that the C1A domain plays a critical role in the DAG-induced membrane binding and activation of PKC␣ (38,65), whereas both the C1A and C1B domains of PKC␥ participate in these processes (38). This is ascribed to the fact that the C1A domain of PKC␣ has higher DAG affinity, whereas both the C1A and C1B domains of PKC␥ have comparable DAG affinity and conformational flexibility.…”
Section: Phosphatidylserine (Ps)-specific Membranementioning
confidence: 96%
“…PS Ͼ PG Ͼ Ͼ PC) (15). Our structure-function analysis of PKC-␣ (15) and its isolated C2 domain (36) and the crystal structure of PKC-␣-C2 (12) suggested that the PS selectivity derive from the specific recognition of PS by a C2 domain-bound calcium ion and several residues located in the calcium binding loops (Fig.…”
Section: Ps Selectivity Of Pkc-␣-c2-mentioning
confidence: 99%
“…Mutagenesis and Protein Expression-The isolated cPLA 2 -␣-C2 and mutants (26) and the isolated PKC-␣-C2 and mutants (15) were expressed and purified as previously described. Mutants of PKC-␣-C2 were generated by the overlap extension PCR (27) using pVL1392-PKC-␣ plasmid as a template (28).…”
Section: Materials-1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholinementioning
confidence: 99%
See 1 more Smart Citation
“…Pioneer studies with the C2A-domain of synaptotagmin I revealed that the C2 domain acts as a Ca 2+ binding motif [6,48,63]. This function has also been demonstrated in several other C2-domaincontaining proteins such as classical PKCs [5,40,41,49], cPLA2 [12,43] and Nedd4 [45] all of which bind to phospholipids in a Ca 2+ -dependent manner. Furthermore, it has recently been found that Ca 2+ forms a bridge between the C2 membrane-binding domain of PKCα and PS [42].…”
Section: Introductionmentioning
confidence: 99%